The Features of a Humoral Immune Response Development during the Acute Phase of ixodes Tick-Borne Borreliosis (Based on Multiplex Analysis with the Immunochip) - V. G. Pomelova; E. I. Korenberg; T. I. Kuznetsova; N. S. Osin (Эпидемиология и вакцинопрофилактика)
The features of development of IgM or IgG immune responses to Borrelia antigens (C6, OspC and VlsE) were studied in 155 patients with localized and disseminated stages of disease with Ixodid Tick-borne Borrelioses (ITBB), the cases of mixed infection with ITBB and human granulocytic anaplasmosis (HGA) including. Patient sera (n = 373) were examined by a multiplex microarray immunoassay test (PHOSPHANTM). At the localized stage of the disease, a positive PHOSPHAN reaction with C6 from B. burgdorferi was observed significantly more frequently in tests for IgG than for IgM at almost all times after tick bite, except for the first week. The frequency of positive samples in tests for both IgM and IgG was higher than for IgG alone, although the difference lacked statistical significance. Positive reactions with OspC or VlsE were observed only in the samples from patients that were also positive for IgM and/or IgG to C6. Therefore, additional detection of IgM to recombinant proteins did not improve significantly the overall sensitivity of the latter PHOSPHAN variant. As compared with ITBB monoinfection, the frequency of positive samples in patients with mixed ITBB + HGA infection was significantly higher (p < 0.05). At the disseminated stage of the disease, the proportion of positive reactions with any of Borrelia antigens for IgM was comparable or higher than for C6-IgG that resulted in a substantial number of patients with negative reactions for IgG; this necessitates the use of alternative methods (e.g., PCR) to exclude false-positive serologic results.